On Elliptic Equations in Orlicz Spaces Involving Natural Growth Term and Measure Data - Mohammed Kbiri Alaoui (Abstract and Applied Analysis)
The paper deals with the existence of solutions of elliptic equations in the framework of Orlicz spaces with right-hand side measure and natural growth term.